Digital Public Services in Indonesia Show High Satisfaction and Adaptation Challenges Remain - Fadillah, Nur; Mursyidah, Lailul (Indonesian Journal of Cultural and Community Development, 2024)
General background: Public service is an essential function of government, aimed at fulfilling citizen needs through the provision of goods, services, and administrative support in accordance with regulations. Effective public service requires continuous bureaucratic reforms. Specific background: Lemujut Village, in collaboration with the Population and Civil Registration Service of Sidoarjo Regency, introduced the Online Service (Plavon) application to improve population administration and civil registration services. However, the effectiveness of the Plavon application remains underexplored. Knowledge gap: There is limited research on the effectiveness of digital public service platforms like Plavon in rural Indonesian settings, particularly in terms of productivity, efficiency, satisfaction, and adaptability. Aims: This study aims to evaluate the effectiveness of the Plavon application in improving public service quality in Lemujut Village by analyzing five key elements: productivity, efficiency, satisfaction, adaptation, and development. Results: Findings indicate that productivity is high, with Plavon operators following procedures and maintaining public trust. However, efficiency is lacking, as some administrative processes fail to meet service time standards. Community satisfaction is notably high at 98.98%, but adaptation to digital services remains suboptimal due to inadequate socialization. Development efforts, such as coordinating via WhatsApp and establishing a call center, show significant progress. Novelty: This study provides a detailed evaluation of the Plavon application’s impact on village-level public services, highlighting the role of digitalization in improving service delivery while identifying challenges in community adaptation and efficiency. Implications: The findings suggest the need for enhanced socialization of digital services and continued development of digital infrastructure to ensure equitable access and efficiency in rural public services. Highlights: High public satisfaction, but service delays persist. Digital adaptation slow due to lack of community awareness. Effective coordination boosts service improvement efforts. Keywords: Public service, digital platform, Plavon, effectiveness, rural Indonesia